Long-Term Results after Fallot Repair - Kleinöder, Jonas Markus; Purbojo, Ariawan; Blumauer, Robert; Cuomo, Michela; Alkassar, Muhannad; Dittrich, Sven; Cesnjevar, Robert (The Thoracic and Cardiovascular Surgeon, 2022)
Background The aim of this study was to evaluate the long-term outcome and freedom from pulmonary valve replacement (PVR) after initial repair of tetralogy of Fallot (TOF).Patients and Methods The cohort of 306 patients treated between 1980 and 2017 was divided into anatomical subgroups according to the diagnosis of TOF-pulmonary stenosis, TOF-pulmonary atresia and TOF-double outlet right ventricle. Patients were treated with transannular patch (TAP), valve sparing repair (VSR), or conduits from the right ventricle to the pulmonary arteries (RVPA conduits).Results There were 21 deaths (6.9%), 14 being hospital deaths (4.6%) after primary correction and four deaths (1.3%) occurred after PVR. One patient died after a non-cardiac operation (0.3%). There were two late deaths (0.7%). During the past 12 years no early mortality has been observed. Ninety-one patients (30.4%) received PVR after a median of 12.1 ± 7.0 years with an early mortality of 4.4% (n = 4) and no late mortality. A significant difference in freedom from reoperation after TAP, VSR, and RVPA-conduits could be identified. Multivariate analysis displayed transannular repair (p = 0.016), primary palliation (p <0.001), the presence of major aortopulmonary collateral arteries (MAPCA; p = 0.023), and pulmonary valve Z-scores < − 4.0 (p = 0.040) as significant risk factors for PVR.Conclusion TOF repair has a beneficial long-term prognosis with low morbidity and mortality. Pulmonary valve Z-scores < − 4.0, transannular repair, and presence of MAPCAs are associated with earlier PVR. Non-VSRs and TOF-pulmonary atresia lead to earlier reoperation but have no negative impact on survival.
Keywords: surgery; incisions; tetralogy of Fallot; reoperation; outcomes; pulmonary valve replacement